Disinformation As A Contemporary Security Threat: A Literature Review - Prasojo; Muhamad Lukman Arifianto; Azhar Irfansyah (KRTHA BHAYANGKARA, 2024)
Disinformation has become a threat to public security and order. Disinformation is a strategy to obscure information by spreading information that is deliberately false and false. Whatever the purpose of disinformation, the public will be the victims. Given its status as a threat, it requires appropriate policing measures to prevent the spread of disinformation. To counter disinformation, it is necessary to develop strategies by empowering communities to counteract disinformation when it occurs. By using the literature review method, this research will show some community empowerment policies that can be done to prevent the spread of disinformation.